Efek Evaporasi Larutan Hasil Kromatografi pada Mobilitas Pembawa Muatan Lapisan Klorofil: Efek Evaporasi Larutan Hasil Kromatografi pada Mobilitas Pembawa Muatan Lapisan Klorofil - Supatmi, Supatmi; Utari, Utari; Budi Purnama, Budi Purnama (Jurnal Fisika dan Aplikasinya, 2025)
Study on charge carrier mobility of Spirulina sp layers I-V meters characterization has been done. The results show that charge carrier mobility increases with the number of layers Spirulina sp. Charge carrier mobility for N > 3 showed a constant value. It is contributed trapping dominant charge carrier layers for the number of iteration more.